2010
DOI: 10.1007/s11999-010-1446-x
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Case of the Month: Ankle Pain and Swelling in a 23-year-old Man

Abstract: A 23-year-old man referred by his primary care physician presented with a 1.5-year history of progressive left ankle pain and swelling. He recalled no history of trauma other than stepping on a horseshoe crab when he was 8 years old and having the tail removed in a local emergency department. He denied recent fevers, chills, night sweats, weight loss, or weight gain. Physical examination revealed substantial nonpitting edema around the hindfoot region extending up the distal 1 .3 of his leg. There was no skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Foreign body penetration injuries are very much common in Middle East region especially in children. Foreign bodies can be retained for a significant time before diagnosis, as high a 15 years [ 1 ]. In our case, the wooden splinter remained asymptomatic for three years.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign body penetration injuries are very much common in Middle East region especially in children. Foreign bodies can be retained for a significant time before diagnosis, as high a 15 years [ 1 ]. In our case, the wooden splinter remained asymptomatic for three years.…”
Section: Discussionmentioning
confidence: 99%
“…14 The incidence of foreign-body granulomas after orthopaedic surgeries has been described to be 0.61%, and these have been reported as isolated cases. 1,2,9,10,[13][14][15][16][17][18][19]23,27 Few articles have reported on suture foreign-body granulomas in the orthopaedic literature (Tables I and II). [14][15][16]18,27 Morimoto et al 16 reported a 2-year history of a left buttock mass that rapidly grew over a period of 2 months after nonabsorbable nylon suture was used to surgically repair a hip dislocation 20 years earlier.…”
Section: Discussionmentioning
confidence: 99%